Direct 1HNMR method for simultaneous determination of total and individual curcuminoids - Durga Prasad; Naresh KS; Aishwarya Praveen; Siva Sankara Reddy Singam; Sachin R. Chaudhari (Food Chemistry Advances, 2022)
Curcuma longa L., usually referred to as turmeric, is an extensively used spice throughout the world. The curcuminoids (a mixture of three components) present in turmeric, as well as their profile, determine its quality. Consequence quantification and profiling of curcuminoids are important. Total quantification and profiling of curcuminoids are commonly done using UV spectroscopy and HPLC, respectively. Today, NMR is a relatively developed area for studying food quality because of its various notable elements. However, its benefits have never been investigated in turmeric quality analysis. The current study explored the possibility of a 1H- NMR-based method for measuring curcuminoids and their profiling. This method has been cross-validated with HPLC and UV analysis. In addition, the application of the proposed method has been demonstrated in turmeric samples from various Indian states. The importance of these studies depends on the evolution of methodologies related to accessible resources.